Health Services Aimed at Serving the Elderly of Peru - González Hunt, César (2016)
This article focuses its attention on the analysis of health services provided to seniors in the framework of public politics must give them rights safeguard Social Security and Health, and their level of access in cases of poverty and others; further analysis of the work of those institutions whose responsibility was granted by the Act of Older Persons for the protection of the same in the joint work with the SIS and Essalud.